A genetically validated approach for detecting inorganic polyphosphates in plants. (13th January 2020) - Zhu, Jinsheng; Loubéry, Sylvain; Broger, Larissa; Zhang, Youjun; Lorenzo‐Orts, Laura; Utz‐Pugin, Anne; Fernie, Alisdair R.; Young‐Tae, Chang; Hothorn, Michael
Summary: Inorganic polyphosphates (polyPs) are linear polymers of orthophosphate units linked by phosphoanhydride bonds. Polyphosphates represent important stores of phosphate and energy, and are abundant in many pro‐ and eukaryotic organisms. In plants, the existence of polyPs has been established using microscopy and biochemical extraction methods that are now known to produce artifacts. Here we use a polyP‐specific dye and a polyP‐binding domain to detect polyPs in plant and algal cells. To develop the staining protocol, we induced polyP granules in Nicotiana benthamiana and Arabidopsis cells by heterologous expression of Escherichia coli polyphosphate kinase 1 (PPK1). Over‐expression of PPK1 but not of a catalytically impaired version of the enzyme leads to severe growth phenotypes, suggesting that ATP‐dependent synthesis and accumulation of polyPs in the plant cytosol is toxic. We next crossed stable PPK1‐expressing Arabidopsis lines with plants expressing the polyP‐binding domain of E. coli exopolyphosphatase (PPX1c), which co‐localized with PPK1‐generated polyP granules. These granules were stained by the polyP‐specific dye JC‐D7 and appeared as electron‐dense structures in transmission electron microscopy sections. Using the polyP staining protocol derived from these experiments, we screened for polyP stores in different organs and tissues of both mono‐ and dicotyledonous plants. While we could not detect polyP granules in higher plants, we could visualize the polyP‐rich acidocalcisomes in the green alga Chlamydomonas reinhardtii . Significance Statement: A chemical dye and an inorganic polyphosphate‐binding domain are shown to specifically label inorganic polyphosphate granules in transgenic Arabidopsis lines and Chlamydomonas acidocalcisomes. Using these tools we show that, in contrast to many prokaryotic and eukaryotic organisms, higher plants do not seem to contain large stores of inorganic polyphosphate.